THE EFFECT OF INDIVIDUAL VALUE ON AFFECTIVE COMMITMENT THROUGH PSYCHOLOGICAL WELL-BEING AS INTERVENING VARIABLES (Study on Members of the Maluku Regional Police State Police School) - Adisti Prita Andian; Intan Ratnawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The most important aspect of the police profession is service to the community. As public servants, the police are required to be able to perform well in terms of these services. The aim of the POLRI itself is to realize domestic security which includes maintaining security and public order, order and upholding the law, the implementation of protection, protection and services to the community, as well as maintaining public peace by upholding human rights. In order to be able to provide satisfaction to society, the police must be good at managing emotionally because in addition to achieving organizational goals, a police officer must also think about his personal well-being. Therefore, it requires organizational commitment, especially high affective commitment from a police officer. This study analyzes the relationship between affective commitment and individual values and psychological well-being due to differences in results in several studies and there are still few studies examining affective commitment, individual values, and psychological well-being in the police sector. The research was conducted at the State Police School of the Maluku Regional Police, totaling 92 employees using the census technique. The data analysis technique used is Partial Least Square (PLS). The results of this study indicate that individual value has a significant positive effect on affective commitment, individual value has a significant positive effect on psychological well-being, and psychological well-being has a significant positive effect on affective commitment. So it can be concluded that to increase affective commitment, it is necessary to increase individual values that can affect a person's psychological well-being. Keyword : Individual Values, Affective Commitment, Psychological Well-being, Police